Isolated abdominal aortic dissection - a different animal? - case series - Rego,Duarte (2021)
Abstract Introduction: Isolated abdominal aortic dissection (IAAD) is a relatively rare event and precise indications for treatment aren't clearly deJned. Its natural history is not fully understood due to the rarity of the disease and to the fact that most surgeons have a low threshold to intervene in these patients. Open surgery represents the classical treatment but endovascular intervention has gained wide acceptance in most centers and is now the most frequently adopted treatment option. The largest series of treated patients are from Asian centers with the largest of them comprising only 33 cases whereas in western surgical centers the largest series contains only 21 patients. Methods: Single center, retrospective, observational, study of patients with IAAD who were treated with open or endovascular surgery. Results: We describe eight patients with IAAD who underwent treatment in our institution (four males and four females). Median age at presentation was 78 years and all patients were asymptomatic. Median aortic diameter at presentation was 30mm (14-85mm). All but one patient underwent endovascular treatment. Three patients were treated with bifurcated aortic endografts, three patients had a single stent-graft (iliac limbs of aortic endografts) implanted and one patient underwent a CERAB procedure for coexistent stenotic disease of the aortic bifurcation. There were no perioperative deaths. Median follow-up was 6,2 years (2 months-13 years). Late reintervention was needed in one patient, 8 years after initial surgery, due to a type 1 endoleak. Conclusion: According to our experience, endovascular intervention represents a safe and durable treatment option in IAAD, however, long-term follow-up is mandatory. Larger studies with longer follow-ups are needed to understand this disease.